Pendulum state estimation using nonlinear state estimators - Naga Anusha, M; Swara, Y; Koteswara Rao, S; Gopi Tilak, V (International Journal of Engineering and Technology, 2018)
The convergence over Non-linear state estimation is not satisfied by Kalman filter. For nonlinear state estimation problems, the present research work on the performance analysis of linearized kalman filter and extended kalman filter for a simple nonlinear state estimation problem. The simple pendulum is the best example for simple nonlinear state dynamics. The performance analysis based on the root mean square errors of the estimates also specified through Monte-Carlo simulation.